Stroll into students' learning: Acts to unload teachers' values through the practices of lesson study for learning community in Vietnam. (July 2018) - Tsukui, Atsushi; Saito, Eisuke
In studies on teacher professional development, the embodiment of teachers' values in professional practice has emerged as an important area of focus. Employing the sociocultural approach, this study discusses the link between teachers' acts and underlying values based on a Vietnamese teacher's detailed field notes on cases of school reform through the introduction of Japanese lesson study for learning community. Drawing on the concepts of inspection and stroll, the study describes the discrepancy between conventional observational acts and emerging ones. Inspection refers to the actions and values held by teachers that underline compliance with the prescribed curriculum and educational bureaucratic procedures, while stroll refers to a disposition that entails actions and values appreciating each pupil's existence and learning as it is, without rigid bureaucratic perspectives. The finding was that the teacher's act of stroll embeds new underlying values in her/his professional work; similarly, how she/he performs a stroll could inform her/his professional knowledge and identity. Lesson study can offer the teacher the experience of seeing self that generates the possible momentum of these parallel shifts.